2021
DOI: 10.1155/2021/7714533
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Antiosteoarthritic Mechanism of Action of Natural Products

Abstract: Background. Osteoarthritis (OA) is a clinical joint degenerative disease, the pathogenic factors of which include age, obesity, and mechanical injury. Its main pathological features include cartilage loss, narrowing of joint space, and osteophyte formation. At present, there are a variety of treatment methods for OA. Natural products, which are gradually being applied in the treatment of OA, are advantageous as they present with low toxicity and low costs and act on multiple targets. Methods. The terms “natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“… 18 , 19 Natural products, including terpenoids, polysaccharides, polyphenols, flavonoids, alkaloids, and saponins, are advantageous as their low toxicity, low costs, and act on multiple targets, are gradually being applied in the treatment of OA. 20 But, the function of AC tissue is largely conferred by its compartmentalized zonal microstructure and composition.…”
Section: Articulate Cartilage Defects Therapeutic Strategiesmentioning
confidence: 99%
“… 18 , 19 Natural products, including terpenoids, polysaccharides, polyphenols, flavonoids, alkaloids, and saponins, are advantageous as their low toxicity, low costs, and act on multiple targets, are gradually being applied in the treatment of OA. 20 But, the function of AC tissue is largely conferred by its compartmentalized zonal microstructure and composition.…”
Section: Articulate Cartilage Defects Therapeutic Strategiesmentioning
confidence: 99%
“…Obesity can lead to joint overload and promote OA development. In addition, mechanical damage to articular cartilage and subchondral bone promotes OA development ( Balahura et al, 2020 ; Gao et al, 2021 ). Part of OA is attributable to inheritance, with hereditary OA due to mutations in collagen type II, IX, or XI ( Kannu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that natural products could regulate glycolysis ( Duya et al, 2022 ; Kooshki et al, 2022 ), interfere with chondrocyte metabolic reprogramming, improve chondrocyte viability, and inhibit OA development. Moreover, natural products have the advantages of low toxicity, low cost and multiple targets ( Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies using herbal and plant extracts to manage OA are encouraging and may provide greater flexibility in clinical settings ( Gao et al, 2021 ; Mu et al, 2021 ). Ginkgo biloba L. extract is widely used worldwide as the first choice botanical medicine for the treatment of heart and brain diseases ( Abad et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%